2023
DOI: 10.1002/anie.202309760
|View full text |Cite
|
Sign up to set email alerts
|

A DNA‐Stabilized Ag1812+ Cluster with Excitation‐Intensity‐Dependent Dual Emission

Abstract: DNA‐stabilized silver nanoclusters (DNA‐AgNCs) are easily tunable emitters with intriguing photophysical properties. Here, a DNA‐AgNC with dual emission in the red and near‐infrared (NIR) regions is presented. Mass spectrometry data showed that two DNA strands stabilize 18 silver atoms with a nanocluster charge of 12+. Besides determining the composition and charge of DNA2[Ag18]12+, steady‐state and time‐resolved methods were applied to characterize the picosecond red fluorescence and the relatively intense mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…In early years, a major bottleneck for metal nanoclusters is that they have rarely demonstrated an unparalleled performance in certain critical applications that no other types of materials can compete. Thus, the recent research progress in the strong near‐infrared photoluminescence from the biocompatible gold and other nanoclusters, [35–55] as well as the high catalytic performance (e.g., CO 2 reduction) of Cu and other emerging nanoclusters [56–72] are very exciting. Different from above work, our previous work demonstrated the first application of metal nanoclusters in 3D laser printing [16] and current findings further manifest the capability of metal nanoclusters as unparalleled photoinitiation systems which could break though the current efficiency limit of 3D laser nanoprinting.…”
Section: Figurementioning
confidence: 99%
“…In early years, a major bottleneck for metal nanoclusters is that they have rarely demonstrated an unparalleled performance in certain critical applications that no other types of materials can compete. Thus, the recent research progress in the strong near‐infrared photoluminescence from the biocompatible gold and other nanoclusters, [35–55] as well as the high catalytic performance (e.g., CO 2 reduction) of Cu and other emerging nanoclusters [56–72] are very exciting. Different from above work, our previous work demonstrated the first application of metal nanoclusters in 3D laser printing [16] and current findings further manifest the capability of metal nanoclusters as unparalleled photoinitiation systems which could break though the current efficiency limit of 3D laser nanoprinting.…”
Section: Figurementioning
confidence: 99%
“…11,28−31 Additionally, steady state approaches do not allow for discriminating between ns-and μs-lived emission, leading to potential misclassification of the training data for dual emissive DNA-AgNCs. 6,8,10,17,32,33 Here, we demonstrate a new technique for screening assynthesized DNA-AgNCs by exciting with the white light output (λ ex ≈ 490−900 nm) of a pulsed supercontinuum laser, which is used together with a common-path interferometer and timecorrelated single photon counting (TCSPC) board for spectrally and temporally resolving the DNA-AgNC emission, respectively. With white light excitation, the DNA-AgNCs are directly excited into their main AgNC-related band, rather than through the DNA-related UV band, providing a more relevant readout of DNA-AgNC emission when used with Vis/NIR excitation at a later stage.…”
mentioning
confidence: 99%
“…In this paper, we will describe the working principle of bmTG-FTS and demonstrate its applicability with an exemplary DNA-AgNC that shows dual emission on the nano-to millisecond timescale. 17 bmTG-FTS is based on three key elements: TCSPC hardware, an interferometer, and a high repetition laser (MHz) that can be switched on and off on a microsecond time scale. Using TCSPC, each detected photon is assigned a 'micro-time' and a 'macrotime' (Fig.…”
mentioning
confidence: 99%
“…For the proof of principle demonstration of bmTG-FTS, we decided to investigate a dual emissive DNA-AgNC, which we recently reported. 17 This particular AgNC is stabilized by the DNA sequence, 5 0 -TGGACGGCGG-3 0 , and mass spectrometry revealed that the cluster has a molecular formula of (DNA) 2 [Ag 18 ] 12+ . 17 It has an absorption maximum at 543 nm and two emission bands, one associated with a ps decay and one with a ms decay.…”
mentioning
confidence: 99%
See 1 more Smart Citation